Physiotherapy Management for Carpal Tunnel Syndrome Bilateral: A Case Study - Putri, Sefrizka Irwhana; Sudaryanto, Wahyu Tri; Ismadi, I (Academic Physiotherapy Conference Proceeding, 2022)
Introduction: Carpal Tunnel Syndrome (CTS) is a disorder of the forearm due to compression of the median nerve in the carpal tunnel, either due to fascial edema in the carpal tunnel or due to abnormalities in the small bones in the palm. Carpal tunnel syndrome (CTS) is the most common upper extremity pressure neuropathy, with a prevalence of 3%-5% in the general population, and is 6% more common in women over 40 years of age. The objectives to be achieved in this study are to reduce the pain complained of by the patient, increase the strength of the muscles around the wrist and optimize the increase in daily functional activities in household work activities.Case Presentation: Mrs. K is female, 47 years old, works as a housewife. Mrs. K complains of pain, numbness, tingling and discomfort in both right and left wrists until they radiate to the upper arm. Complaints become worse when buttoning clothes, opening bottles, washing clothes which activities involve movement of the fingers.Management and Outcome: Patients do therapy twice a week for two weeks with physiotherapy programs of ultrasound therapy, stretching exercises, strengthening exercises, and manual therapy. Patients were evaluated using the Numerical Rating Scale (NRS) to measure pain, Manual Muscle Testing (MMT) to measure muscle strength, and the Boston Carpal Tunnel Syndrome Questionnaire (BCTSQ) to measure functional ability.Discussion: Ultrasound produces a warm effect that increases blood circulation and reduces pressure on the median nerve which can reduce pain. Strengthening Exercise by using Hand Exercise with Ball which is able to increase muscle strength, balance, and blood flow to the hand, wrist, and elbow. The manual therapy carried out is Median Nerve Mobilization and Nerve and Tendon Gliding which aims to reduce pressure on the median nerve at the wrist by returning the anatomical structure to its original position.Conclusion: Physiotherapy programs for Bilateral Carpal Tunnel Syndrome patients using Ultrasound Therapy, Stretching Exercises, Strengthening Exercises and Manual Therapy interventions can reduce pain, increase muscle strength and improve functional abilities.